Consider the equation below. X2 + y2 − 2x − 4y − z + 5 = 0 reduce the equation to one of the standard forms. Classify the surface. Ellipsoid elliptic paraboloid hyperbolic paraboloid cone hyperboloid of one sheet hyperboloid of two sheets sketch the surface. Webassign plot webassign plot webassign plot webassign plot

Respuesta :

we are given

[tex]x^2+y^2-2x-4y-z+5=0[/tex]

standard form:

We will complete x , y and z square

make all x , y and z terms together  

[tex]x^2-2x+y^2-4y-z+5=0[/tex]

[tex]x^2-2x+y^2-4y-z=-5[/tex]

[tex]x^2-2*1*x+y^2-2*2*y-z=-5[/tex]

[tex]x^2-2*1*x+1^2+y^2-2*2*y+2^2-z=-5+1^2+2^2[/tex]

[tex](x-1)^2+(y-2)^2-z=0[/tex]

[tex]z=(x-1)^2+(y-2)^2[/tex]

surface:

It is an infinite paraboloid

graph:


Ver imagen rejkjavik

Paraboloids are generated by rotating a parabola across its axes.

  • The equation of the paraboloid is: [tex]\mathbf{z = (x- 1)^2 + (y - 2)^2}[/tex]
  • The surface is an infinite paraboloid

The equation is given as:

[tex]\mathbf{x^2 + y^2 - 2x - 4y - z + 5 = 0}[/tex]

Rewrite as:

[tex]\mathbf{x^2 - 2x+ y^2 - 4y - z + 5 = 0}[/tex]

Add 0 to both sides

[tex]\mathbf{x^2 - 2x + 0+ y^2 - 4y - z + 5 = 0 + 0}[/tex]

Express 0 as the difference between the squares of half the coefficient of x

[tex]\mathbf{x^2 - 2x + (\frac{2}{2})^2 - (\frac{2}{2})^2 + y^2 - 4y - z + 5 = 0 + (\frac{2}{2})^2 - (\frac{2}{2})^2}[/tex]

Cancel out the negative term

[tex]\mathbf{x^2 - 2x + (\frac{2}{2})^2 + y^2 - 4y - z + 5 = 0 + (\frac{2}{2})^2 }[/tex]

Simplify

[tex]\mathbf{x^2 - 2x + 1 + y^2 - 4y - z + 5 = 0 +1 }[/tex]

[tex]\mathbf{x^2 - 2x + 1 + y^2 - 4y - z + 5 = 1}[/tex]

Express as squares

[tex]\mathbf{(x- 1)^2 + y^2 - 4y - z + 5 = 1}[/tex]

Repeat the same process for y

[tex]\mathbf{(x- 1)^2 + y^2 - 4y + (2)^2 - z + 5 = 1 + (2)^2}[/tex]

[tex]\mathbf{(x- 1)^2 + y^2 - 4y + 4 - z + 5 = 1 + 4}[/tex]

[tex]\mathbf{(x- 1)^2 + y^2 + (y - 2)^2 - z + 5 = 1 + 4}[/tex]

[tex]\mathbf{(x- 1)^2 + (y - 2)^2 - z + 5 = 1 + 4}[/tex]

[tex]\mathbf{(x- 1)^2 + (y - 2)^2 - z + 5 = 5}[/tex]

Subtract 5 from both sides

[tex]\mathbf{(x- 1)^2 + (y - 2)^2 - z = 0}[/tex]

Make z the subject

[tex]\mathbf{z = (x- 1)^2 + (y - 2)^2}[/tex]

The above equation is the surface of an infinite paraboloid

See attachment for the sketch of the equation.

Read more about paraboloid at:

https://brainly.com/question/14956045

Ver imagen MrRoyal